2022
DOI: 10.1186/s12885-022-10091-8
|View full text |Cite
|
Sign up to set email alerts
|

2011–2021 rising prevalence of HPV infection among oropharyngeal carcinoma in France

Abstract: Background The objective of our study was to investigate changes over the past decade in patient age and the prevalence of HPV in the population of patients with oropharyngeal carcinoma (OPC) treated at our center. Methods We performed a retrospective cohort study of patients treated at our cancer center for OPC between 2011 and 2021. Tissue biopsies were assessed for HPV status based on p16 staining for all patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Nonetheless, the overall increase in the incidence of oropharyngeal tumors observed in the last decades in our country [27,28] suggests that there is a real increase in the incidence of HPV-driven lesions. These results are consistent with recent trends observed in other European geographical areas including the Netherlands, France, Denmark, Sweden, and Southern Europe [2,[29][30][31][32][33][34][35], with the growing prevalence of oral HPV infection due to changes in sexual habits likely being responsible for the observed epidemiological trends in oropharyngeal cancer [36].…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, the overall increase in the incidence of oropharyngeal tumors observed in the last decades in our country [27,28] suggests that there is a real increase in the incidence of HPV-driven lesions. These results are consistent with recent trends observed in other European geographical areas including the Netherlands, France, Denmark, Sweden, and Southern Europe [2,[29][30][31][32][33][34][35], with the growing prevalence of oral HPV infection due to changes in sexual habits likely being responsible for the observed epidemiological trends in oropharyngeal cancer [36].…”
Section: Discussionsupporting
confidence: 90%
“…In the United States, the incidence of HPV-positive OPC has increased by 225% among young men in the last two decades [ 9 ]. In Europe, a similar trend has been observed, with incidence rates of HPV-positive OPC increasing by approximately 60% among young men in the last 10 years [ 10 ].…”
Section: Introductionsupporting
confidence: 62%
“…Higher prevalence of oral HPV among older adults has been previously reported and may be due to increased HPV exposure, infection and/or persistence with age, potential loss of immune control, and/or reactivation of latent HPV infections . Recent studies have also reported that median age at diagnosis for HPV-related OPC is increasing, and that among patients 65 years and older, the proportion of HPV-related OPC increased from 41% during 1995 to 2000 to 75% during 2007 to 2013 . Reasons behind this trend are not fully understood, but it is therefore not surprising to observe an increased prevalence of oral HPV infection in middle-aged and older men, as HPV predates OPC occurrence.…”
Section: Discussionmentioning
confidence: 98%